Level of Sexual and Reproductive Health Knowledge and Attitude Among Early Adolescent - Abd Aziz, Karimah Hanim; Aida Jamani, Nurjasmine; Lahasan, Nur Wajihah; Che Ujang, Syazwana Amirah; Hanafiah, Nur Ili Dalia Mohd Ali (IIUM Medical Journal Malaysia, 2018)
Introduction: Topic on sexuality has largely remained a taboo subject for discussion between parents and their children in Malaysia, which might contributed to increase sexual activity among adolescent age group. This study was undertaken to assess the level of knowledge, attitude and their associated factors among standard 4 and 5 students in a primary school in Kuantan, Pahang. Materials and Methods: A cross-sectional study was conducted involving 281 students from standard 4 and 5 students using a self-administered validated Malay version KAPSRH questionnaire. Universal sampling was used for selection of students who fulfilled the inclusion and exclusion criteria. Descriptive statistics was used to explain respondents’ background characteristics and multiple logistic regression was used to find the association. Results: Of the 252 students completed the surveys, 135 were males and 117 were females with the mean age of 10.47. It was found that more that half students reported to have good knowledge (56.3%) and attitude (59.4%) towards sexual and reproductive health. Year of study (p<0.0001), involvement in religious activities (p<0.0001) and household income were associated with both knowledge and attitude. While prayers (p=0.04), practice fasting (p=0.03), mothers’ education (p<0.0001), fathers’ education (p<0.0001) and fathers’ working status (p=0.04) were associated with good attitude only. Conclusion: Although majority of the students have good level of sexual and reproductive health knowledge and attitude , there is still room for improvement. Parents, schools and health care providers are challenged with the task of providing adolescents with accessible sexual and reproductive health information to promote healthy sexual and reproductive lives.